ANALISIS PENGARUH CASH DIVIDEND, FREE CASH FLOW, RETURN ON ASSET, DAN ECONOMIC VALUE ADDED TERHADAP HARGA SAHAM (Studi Perusahaan Manufaktur di Bursa Efek Indonesia) - Rosdiana, Rosdiana (Perpustakaan dan Penerbitan Unismuh Makassar, 2011)
The aims of the research are to find out whether Cash Dividend, Free Cash Flow, Return On Assets, and Economic Value Added simultaneously and partially have an influence on stock prices. And to find out the most dominant variable affecting stock price. The sample was selected by using purpossive sampling technique. The Method of analysis to test the hypothesis was Multiple Linear Regression.The results of the research reveal that cash dividend and economic value added partially have a significant influence on stock prices at the significance level of less than 5% (respectively 0.0% and 1.0% respectively); free cash flow and return on assets was partially do not have a significant influence on stock price at the significant level of more than 5% (29.6% and 21.0% respectively), but they simultaneously have a significant influence on stock price of manufacture companies in Indonesia Stock Exchange at the level of less than 5% (0.0%). Cash dividend and economic value added are used by the investors to predict the stock price of the companies of manufacture companies listed in Indonesia Stock Exchange from 2005 to 2009, while free cash flow and return on assets have a weak influence prediction capability of cash dividend, free cash flow, return on asset, and economic value added on stock price is 87,7%.